Pengembangan Rencana Pelaksanaan Pembelajaran Model Problem Based Learning Daring untuk Meningkatkan Motivasi Belajar Siswa Materi Perubahan Lingkungan: (Development of Online Problem Based Learning Implementation Plans to Increase Student Motivation on Environmental Change Materials) - Roni Handika Putra; Asrial Asrial; Jefri Marzal (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2021)
The design of RPP model PBL online in biology learning is very necessary, the reason is because in biology there is a lot of material that requires the design of online PBL model lesson plans to facilitate the delivery of material by teachers to students. The application of the RPP model PBL online can be used by the teacher as a guide in learning. The reason is because of the lack of teacher guidelines in designing RPP model PBL online lesson plans. Efforts that can be made to overcome this problem are by designing the optimal RPP model PBL online. The purpose of this research is to produce a product, determine the development process and feasibility and to determine the increase in student motivation after online learning. This research is a development research. The research design follows the ADDIE development model which consists of 5 stages, namely analysis, design, development, implementation and evaluation. Products RPP model PBL online before being tested are first validated by expert lecturers using a 3-stage validation questionnaire with the final percentage acquisition of 88.75% with a very valid category, can be used without revision. After that the product of the RPP model PBL online was given to 2 biology subject teachers to see perceptions, using the teacher's perception questionnaire, the results obtained were 84.37% with a very good category, thus the RPP model PBL online was said to be feasible to be applied in learning. Furthermore, online learning is carried out in large groups of class kelas MIPA 1 students consisting of 20 students. After the trial was carried out, students were given a motivation questionnaire and obtained results with a percentage of 81.87% in the very good category. From the test results obtained, it can be concluded that the development of RPP model PBL online lesson plans can increase student learning motivation. Abstrak. Rancangan RPP model PBL daring dalam pembelajaran biologi sangat diperlukan, alasannya karena pada mata pelajaran biologi banyak sekali materi yang memerlukan rancangan RPP model PBL daring untuk mempermudah dalam penyampaian materi oleh guru kepada siswa. Penerapan RPP model PBL daring dapat digunakan guru sebagai pedoman dalam pembelajaran. Alasannya, karena minimnya pedoman guru dalam merancang RPP model PBL daring. Upaya yang dapat dilakukan untuk mengatasi hal teersebut adalah dengan merancang RPP model PBL daring secara maksimal. Tujuan penelitian ini adalah untuk menghasilkan produk, mengetahui proses pengembangan dan kelayakan serta untuk mengetahui peningkatan motivasi siswa setelah pembelajaran daring. Penelitian ini merupakan penelitian pengembangan. Desain peneltian mengikuti model pengembangan ADDIE yang terdiri dari 5 tahap yaitu analisis, desain, pengembangan, implementasi dan evaluasi. Produk RPP model PBL daring sebelum diujicobakan terlebih dahulu divalidasi oleh dosen ahli menggunakan angket validasi sebanayak 3 tahap dengan perolehan persentse akhirÂ 88,75% dengan kategori sangat valid, dapat digunakan tanpa revisi. Setelah itu produk RPP model PBL daring diberikan kepada 2 guru mata pelajaran biologi untuk melihat persepsi, menggunakan angket persepsi guru, diperoleh hasil dengan persentase 84,37% dengan kategori sangat baik, dengan demikian RPP model PBL daring dikatakan layak diterapkan dalam pembelajaran. Selanjutnya pembelajaran daring dilaksanakan pada kelompok besar siswa kelas Î§ MIPA 1 yang terdiri dari 20 orang siswa. Setelah uji coba dilaksanakan siswa diberikan angket motivasi dan memperoleh hasil dengan persentase 81,87% dengan kategori sangat baik. Dari hasil uji coba yang diperoleh dapat disimpulkan bahwa pengembangan RPP model PBL daring dapat meningkatkan motivasi belajar siswa.